2011
DOI: 10.4162/nrp.2011.5.6.503
|View full text |Cite
|
Sign up to set email alerts
|

The anti-obesity effect ofLethariella cladonioidesin 3T3-L1 cells and obese mice

Abstract: The aim of this study was to investigate whether a water extract of L. cladonioides (LC) has an anti-obesity effect in 3T3-L1 cells and obese mice. Treatment of differentiated 3T3-L1 adipocytes with LC caused a significant increase in glycerol release and reduced the protein expression of the adipogenic transcription factors, PPARγ and C/EBPα. In an animal model, obese mice were artificially induced by a high fat diet for 10 weeks. Experimental groups were treated with LC (100 mg/kg/day) by gavage for the next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The process where preadipocytes differentiate into lipid‐laden adipocytes is called adipogenesis, occurs in several stages, including preadipocyte cell proliferation, differentiation and lipid accumulation and transcription factors such as peroxisome proliferator activated receptor gamma (PPARγ) and CCAAT/enhancer binding proteins (C/EBPs) regulates this process (K. N. Kim et al., ; M. Kim, Park, Song, & Cha, ). Lipogenesis is the process of triglyceride (TG) synthesis, which requires enzymes including acetyl CoA carboxylase (ACC) and fatty acid synthase (FAS) (Sung et al., ). Conversely, in the process of breaking down fat, known as lipolysis, adipose triglyceride lipase (ATGL) and hormone‐sensitive lipase (HSL) are required (J. H. Kim et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process where preadipocytes differentiate into lipid‐laden adipocytes is called adipogenesis, occurs in several stages, including preadipocyte cell proliferation, differentiation and lipid accumulation and transcription factors such as peroxisome proliferator activated receptor gamma (PPARγ) and CCAAT/enhancer binding proteins (C/EBPs) regulates this process (K. N. Kim et al., ; M. Kim, Park, Song, & Cha, ). Lipogenesis is the process of triglyceride (TG) synthesis, which requires enzymes including acetyl CoA carboxylase (ACC) and fatty acid synthase (FAS) (Sung et al., ). Conversely, in the process of breaking down fat, known as lipolysis, adipose triglyceride lipase (ATGL) and hormone‐sensitive lipase (HSL) are required (J. H. Kim et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Kim, Park, Song, & Cha, 2015). Lipogenesis is the process of triglyceride (TG) synthesis, which requires enzymes including acetyl CoA carboxylase (ACC) and fatty acid synthase (FAS) (Sung et al, 2011). Conversely, in the process of breaking down fat, known as lipolysis, adipose triglyceride lipase (ATGL) and hormone-sensitive lipase (HSL) are required (J. H. .…”
Section: Introductionmentioning
confidence: 99%
“…1C ). Similarly, Sung et al ( 18 ) found that lichen Lethariella cladonioides (25~500 μg/mL) significantly inhibited lipid accumulation in 3T3-L1 adipocytes. Thus, the TV extract appeared to negatively mediate lipid accumulation, even when applied in low doses, thereby leading to greater inhibition of 3T3-L1 adipocytes differentiation than Lethariella cladonioides .…”
Section: Resultsmentioning
confidence: 79%
“…In the context of adipogenesis, AM-879 did not induce the expression of the adipogenic markers genes, Cebpa and Cd36 ( 50 , 51 ), in 3T3-L1 cells, which contrasted with the effect of the full PPARγ agonist, Rosi, which, as expected, strongly increased the expression of these genes ( 9 , 45 , 52 ). Cells treated with AM-879 present similar levels of mRNA, in comparison to control cells, for the key regulator of adipogenesis CEBPA, which together with PPARγ, is essential during the early stage of adipocyte differentiation ( 53 ), and in the maintenance of this state ( 54 , 55 ). Cd36 , another important gene in lipid metabolism that is also a direct target of PPARγ ( 56 ), showed slightly reduced mRNA expression after AM-879 treatment.…”
Section: Discussionmentioning
confidence: 99%